EFEKTIVITAS KURIKULUM MERDEKA DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM DI SMP TERPADU DI KABUPATEN JOMBANG - ABIDIN, MOHAMMAD KHOIRUL; Achadi, Muh. Wasith (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
This article describes the effectiveness of the independent curriculum which includes the implementation of the independent curriculum, improving the quality of PAI, and the effectiveness of the independent curriculum in PAI learning. the independent curriculum is a solution provided by the ministry of education and research to develop the potential of students and improve the quality of post-pandemic education. there are four major changes in the independent curriculum, namely a flexible curriculum, focusing on essential material, using various teaching tools, and utilizing digital technology. The research is descriptive qualitative. The method of extracting data through interviews using a structured interview instrument guide. Data analysis through data reduction by clarifying and sharpening research results, presenting data in descriptive form, and verifying data or drawing conclusions from interviews, observations, and literature review results. The research results show: The effectiveness of the independent curriculum in Islamic Religious Education subjects does not yet have an effective final increase because it is still in the process of adjustment. But every semester has improved well, both in terms of the learning process or in terms of practicum in the form of projects.